Electron microscopic study of glomerular filtration barrier in the rat kidney embedded in polymerized glutaraldehyde-urea - Prasert Sobhon (2018)
Embedding kidney in polymerized glutaraldehyde-urea favors the retention of glycoprotein matrix of the cell coat and the basement membrane of the glomeruli. The basement membrane appears as a single layer with uniform amorphous matrix. Thick glycoprotein coat covers the whole surface of prodocytes and their foot processes. In areas other than the slits and the portion of the foot processes which touch on the basement membrane, the coat is a continuous layer with an average thickness of 490 Å. In the slits between the foot processes of podocytes there is an actual fusion of glycoprotein coats; the average width of the slit is 415 Å. The glycoprotein ‘plugs’ in the slit may be a significant portion of the glomerular filtration barrier against macromolecules, together with the basement membrane and the slit diaphragms. © 1979 S. Karger AG, Basel.